THE AUTHOR'S REINTERPRETATION OF PHRASEOLOGICAL UNITS WITHIN THE IDIOLECT OF V.S. VYSOTSKY - Odiljon kizi, Shukurova Olmakhon (PT. Antis International Publisher, 2025)
Objective: The lyrical and linguistic self-representation of the author plays a central role in shaping poetic meaning, particularly in the works of V. Vysotsky, a renowned Soviet-era poet and performer. While Vysotsky’s cultural and performative legacy has been widely studied, the nuanced interplay between his poetic voice and linguistic techniques remains underexplored, especially in relation to how his personal identity is encoded through stylistic and colloquial devices. Method: The study employs a qualitative textual analysis of selected poetic works by Vysotsky, focusing on narrative structure, stylistic markers, lexical choices, and figurative language to trace the linguistic features that construct the author's presence. Results: The analysis demonstrates that Vysotsky’s poetic persona is shaped through a close interconnection with his protagonists, whose speech is grounded in colloquial Russian and infused with expressive, ironic, and ambiguous language. His signature style includes transformed idiomatic expressions, self-irony, and metaphorical constructs that blur the line between the author and the character. These stylistic devices contribute to a vivid, authentic voice that mirrors the poet’s personal worldview, positioning the lyrical protagonist as an extension not a contrast of the author. Novelty: This study deepens the understanding of authorial representation in lyrical poetry and underscores Vysotsky’s contribution to modern Russian poetic discourse through his distinctive blend of colloquialism and stylistic innovation.